PENILAIAN LAPORAN KINERJA KEUANGAN PADA PT. PLN (PERSERO) - Sutiara, Silfa Sutiara; Diana, Fina; Mannaga, Idham (Universitas Patria Artha, 2025)
This study aims to examine, identify, and evaluate the financial health of PT. PLN (Persero) by analyzing key financial ratios. The assessment focuses on four main categories: Profitability Ratios (Return on Equity/ROE and Return on Investment/ROI), Liquidity Ratios (Cash Ratio and Current Ratio), Activity Ratios (Loan Rate and Reserve Rate), and Solvency Ratios (Capital to Total Assets Ratio). The evaluation is conducted in accordance with the standards outlined in the Decree of the Minister of State-Owned Enterprises No: KEP-100/MBU/2002. A descriptive method with a quantitative approach is employed in this research. The data analyzed consists of PT. PLN (Persero)’s financial statements for the period of 2020 to 2022, using financial ratio analysis as the main analytical tool. The findings indicate that the financial performance of PT. PLN (Persero) during the 2020–2022 period was classified as less sound, receiving a BB rating. This assessment is based on the financial ratio benchmarks set by the Ministry of StateOwned Enterprises and reflects the overall financial condition of the company.